Legal Protection for Small and Medium Enterprises (SMEs) in Facing Unfair Business Competition - Putri Indah Lestari; Wardi Wardi; Tatang Basujata; Alip Rahman; Diky Dikrurahman (Journal Research of Social Science, Economics, and Management, 2024)
In the context of toxic business competition, this research investigates the legal protection of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in partnerships with large corporations. The primary emphasis is on the implementation of Law Number 5 of 1999, which prohibits monopolistic practices and unfair business competition, and Law Number 20 of 2008, which pertains to small and medium-sized enterprises. Data was collected from literature studies, pertinent regulations, and in-depth interviews with relevant stakeholders using a qualitative approach and a case study design. The research results show that although the legal framework already exists, effective implementation still requires improvement. MSMEs face various challenges in partnerships with large companies, including access to resources and greater risks in business transactions. Recommendations are prepared to strengthen legal protection through regulatory revisions, strengthening legal institutions, legal education, developing partnerships, and stricter law enforcement. The main aim is to increase fairness in business relations between MSMEs and large companies, as well as support inclusive and sustainable economic growth in Indonesia. It is hoped that the implications of this research can provide a positive contribution in renewing policies that support the development of MSMEs as the backbone of the national economy.